Sustainable diets, from design to implementation by multi-objective optimization-based methods and policy instruments - Bashir Bashiri; Bashir Bashiri; Aleksei Kaleda; Raivo Vilu; Raivo Vilu (Frontiers in Sustainable Food Systems, 2025)
The growing concerns over climate change, food security, and public health necessitate a transition toward sustainable diets. However, designing diets that are simultaneously healthy, environmentally friendly, culturally acceptable, and affordable presents significant challenges. This review explores the potential of multi-objective optimization (MOO) as a tool for sustainable diet design and a central element of implementation of optimized diets. MOO allows researchers to balance conflicting objectives, such as minimizing environmental impact while maintaining cultural acceptability and economic feasibility in design and implementation of healthy diets. The review highlights the limitations of traditional single-objective optimization and emphasizes the need for population-specific dietary recommendations using MOO. Furthermore, the paper identifies barriers to sustainable diet adoption and outlines policy solutions to facilitate dietary transitions. Finally, it underscores the need for the development and implementation of flexible national dietary guidelines to incorporate optimization methods for enhanced sustainability. By integrating mathematical modeling, behavioral insights, and policy interventions, this review outlines a holistic approach to development sustainable food systems capable for meeting efficiently global challenges.